ANALISIS PEMAHAMAN KRITERIA GREEN TOLL ROAD OLEH STAKEHOLDER PADA PEMELIHARAAN EKSISTING JALAN TOL BALI MANDARA - Ni Made Sintya Rani; Anak Agung Putri Indrayanti (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
The implementation of road construction and maintenance has begun to apply the concept of green standards or environmentally friendly concept. One of the toll roads currently carrying out road maintenance with the Green Toll Road concept is the Bali Mandara Toll Road. Understanding by stakeholders of the Green Toll Road concept is considered important in sustainable development. The method used in this analysis is the Severity Index method and a survey using a questionnaire distributed to respondents involved in toll road maintenance, both contractors and owners. The research variable used in this study comes from the rating tools system that has been used in Indonesia, namely the Green Road Rating by the Ministry of PUPR in 2018. The study uses a Likert scale of 1-5 in determining the level of agreement. From the results of a questionnaire survey of respondents and an analysis of all indicators, the average value of each indicator in each category will be obtained. The understanding of the organizers (Owners) of the maintenance of the Bali Mandara toll road on the Green Toll Road concept on each criterion is included in the